2015
DOI: 10.1681/asn.2015030268
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dialysate Calcium Level Reduces Progression of Coronary Artery Calcification and Improves Low Bone Turnover in Patients on Hemodialysis

Abstract: Exposure to high Ca concentrations may influence the development of low-turnover bone disease and coronary artery calcification (CAC) in patients on hemodialysis (HD). In this randomized, controlled study, we investigated the effects of lowering dialysate Ca level on progression of CAC and histologic bone abnormalities in patients on HD. Patients on HD with intact parathyroid hormone levels #300 pg/ml receiving dialysate containing 1.75 or 1.50 mmol/L Ca (n=425) were randomized to the 1.25-mmol/L Ca (1.25 Ca; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 46 publications
3
63
1
2
Order By: Relevance
“…Therefore, these results suggest that the lowering of dialysate Ca concentration improved bone remodeling in HD patients with probable lowturnover bone disease. In accordance with these results, Ok et al (8) recently reported that lowering dialysate Ca concentration improved low-turnover bone disease by bone biopsy.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, these results suggest that the lowering of dialysate Ca concentration improved bone remodeling in HD patients with probable lowturnover bone disease. In accordance with these results, Ok et al (8) recently reported that lowering dialysate Ca concentration improved low-turnover bone disease by bone biopsy.…”
Section: Discussionsupporting
confidence: 62%
“…In a recent randomized controlled study, effect of lowering the dialysate calcium level on the progression of CAC and the histologic bone abnormalities in 425 hemodialysis patients was examined [119]. As a result, progression rate of CAC was significantly lower in the low calcium dialysate (1.25 mmol/l) group than in the high calcium dialysate (1.75 mmol/l) group.…”
Section: Dialysate Modificationmentioning
confidence: 99%
“…No changes in H-DCa were found. At the end of follow-up, L-DCa group showed higher bone formation rate, trabecular thickness, and bone volume than H-DCa [20].…”
Section: Dialysis Schedulementioning
confidence: 83%